Women's views and postpartum follow-up in the CHIPS Trial (Control of Hypertension in Pregnancy Study). (November 2016) - Vidler, Marianne; Magee, Laura A.; von Dadelszen, Peter; Rey, Evelyne; Ross, Susan; Asztalos, Elizabeth; Murphy, Kellie E.; Menzies, Jennifer; Sanchez, Johanna; Singer, Joel; Gafni, Amiram; Gruslin, Andrée; et al.
Abstract: Objective: To compare women's views about blood pressure (BP) control in CHIPS (Control of Hypertension In Pregnancy Study) (NCT01192412 ). Design: Quantitative and qualitative analysis of questionnaire responses. Setting: International randomised trial (94 sites, 15 countries). Population/sample: 911 (92.9%) women randomised to 'tight' (target diastolic blood pressure, 85 mmHg) or 'less tight' (target diastolic blood pressure, 100 mmHg) who completed questionnaires. Methods: A questionnaire was administered at ∼6–12 weeks postpartum regarding post-discharge morbidity and views about trial participation. Questionnaires were administered by the site co-ordinator, and contact was made by phone, home or clinic visit; rarely, data was collected from medical records. Quantitative analyses were Chi-square or Fisher's exact test for categorical variables, mixed effects multinomial logistic regression to adjust for confounders, and p  < 0.001 for statistical significance. NVivo software was used for thematic analysis of women's views. Main outcome measures: Satisfaction, measured as willingness to have the same treatment in another pregnancy or recommend that treatment to a friend. Results: Among the 533 women in 'tight' ( N  = 265) vs. 'less tight' ( N  = 268) control who provided comments for qualitative analysis, women in 'tight' (vs. 'less tight') control made fewer positive comments about the amount of medication taken (5 vs. 28 women, respectively) and intensity of BP monitoring (7 vs. 17, respectively). However, this did not translate into less willingness to either have the same treatment in another pregnancy (434, 95.8% vs. 423, 92.4%, respectively; p  = 0.14) or recommend that treatment to a friend (435, 96.0% and 428, 93.4%, respectively; p  = 0.17). Importantly, although satisfaction remained high among women with an adverse outcome, those in 'tight' control who suffered an adverse outcome (vs. those who did not) were not consistently less satisfied, whereas this was not the case among women in 'less tight' control among whom satisfaction was consistently lower for the CHIPS primary outcome ( p  < 0.001), severe hypertension ( p  ≤ 0.01), and pre-eclampsia ( p  < 0.001). Conclusions: Women in 'tight' (vs. 'less tight') control were equally satisfied with their care, and more so in the face of adverse perinatal or maternal outcomes.